Efeitos cumulativos do comprometimento cognitivo, da fragilidade, do estresse e da sobrecarga sobre o risco para mortalidade, hospitalizações, quedas e declínio funcional em idosos cuidadores: follow-up de quatro anos - Bregola, Allan Gustavo (Universidade Federal de São Carlos, 2020)
Introduction: The simultaneous occurrence of cognitive impairment and physical frailty is considered a risk factor for negative health outcomes in older adults, such as falls, hospitalization, and death. In the context of caring, stress and burden are also added as causes of such outcomes. However, there is no evidence that the conditions mentioned - when cumulated – constitute a health risk and exert effects on negative outcomes among older adults who provide care to other older adults in Brazil. Aims: The purpose of this thesis was to analyse the effects of physical frailty, cognitive impairment, burden, and perceived stress on all-cause mortality, the occurrence of hospitalizations and falls in the previous year, and functional decline in community-dwelling older carers from the standpoint of the accumulation of clinical conditions. To meet the larger objective, four studies were conducted with the following aims: (1) to analyse the relation between cognitive impairment and frailty criteria in a general sample of older persons; (2) explore whether these two clinical conditions have effects on functional decline, falls, and hospitalizations in a sample of older adults; (3) analyse whether there are cumulative effects of these two conditions and whether adding the burden of care and perceived stress would increase the risk of hospitalization and four-year mortality in a sample of older carers; and (4) calculate mortality rates for carers and non-carers and explore the effects of gender, age, and education. Configuration and Design: Four manuscripts are presented with results regarding each the aims listed above. The first study is cross-sectional and the other three are longitudinal. Participants: The sample is from studies conducted between 2014 and 2018 at primary care services in the city of São Carlos, state of São Paulo, Brazil. Data collection involved a broad, geriatric-gerontological assessment of 702 participants, including data from 351 carers and their respective 351 older care recipients (non-carers). Questionnaires and Variables: At baseline, global and specific cognitive functions (Addenbrooke Cognitive Examination Battery [ACE-R] and Mini Mental State Examination [MMSE]), physical frailty (five Cardiovascular Health Study criteria), and self-reported psychological/emotional well-being (Perceived Stress Scale and Zarit Burden Interview – brief version) were the main variables collected. Cumulative effects were defined when the participants concomitantly exhibited cognitive impairment, physical frailty, care burden, and a high level of perceived stress at baseline. During follow-up, information was collected on the occurrence of falls, hospitalization, and death. At both moments of the study, the participants answered the Katz Index and the Lawton and Brody Questionnaire to enable the determination of functional decline. Analysis and Statistics: We used analyses that met the research proposal for each study. Mean and standard deviation values were calculated. Survival analyses and controlled, multivariate analyses were performed with distinct categorizations of variables. Results: (1) We analysed data from 667 older adults, 13% of whom had the simultaneous occurrence of cognitive impairment and physical frailty. The chances of cognitive impairment increased by up to 330% in frail individuals and 70% in pre-frail individuals. The physical frailty criteria associated with cognitive impairment were slowness and fatigue. (2) We analysed data from 405 older adults and found that cognitive impairment was associated with future hospitalization and functional decline in two instrumental activities of daily living (IADL). Physical frailty was also associated with these outcomes as well as the occurrence of falls. Both accumulated conditions were associated with hospitalization and decline in three IADLs but not falls after four years. (3) We analysed information on 33 older carers who had deceased and 228 surviving older carers. Among the survivors, 24% were admitted to hospital in the previous year and this outcome was associated with the accumulated conditions of cognitive impairment and frailty, cognitive impairment and stress as well as cognitive impairment and burden, frailty, and stress. The mortality rate was higher among the frail older carers (33.3%), those with cognitive impairment (23.1%), and those with perceived stress (20.4%). Among the accumulated conditions, frail and cognitively impaired carers had a higher mortality rate (43.8%), followed by stressed and cognitively impaired carers (32.4%). (4) We analysed data on 261 carers and 279 non-carers. The four-year mortality rate was 12.6% among the carers and 31.2% among the non-carers. The time of death was similar between the groups – on average two years after baseline. No mortality patterns were found for the group of older carers regarding demographic characteristics. However, death was more frequent among women in the older carer group and occurred within a shorter time interval from baseline among the men in this group. Implications/Discussion: The present results are in agreement with findings described in the literature regarding the close relation between cognitive impairment and physical frailty and that these conditions are independently and cumulatively associated with a worsening general health status and other negative outcomes, such as functional decline, hospitalization, and death in the general population of older adults. This is a pioneering study, as is shows that these conditions can also be seen as indicators of health risk among older persons who provide care to other older persons. Moreover, these inherent clinical conditions of ageing may interact with the strain of providing care (burden and stress) and make older carers more vulnerable than non-carers. In general, older carers had fewer adverse health outcomes compared to non-carers, but the mortality rate of frail carers was similar to that of non-carers. Older carers with concurrent cognitive impairment, frailty, and stress had higher mortality rates than older non-carers. Conclusion: There is a consensus that providing care is as a protective factor against adverse health events. However, when providing care generates stress and burden, carers can become as vulnerable as their peers who do not provide care. The present results are in agreement with data described in the literature and contribute new knowledge that the conditions often found in the population of older adults, such as frailty and cognitive impairment, can make older carers more vulnerable than non-carers.
Cumulative effects of cognitive impairment, frailty, stress and burden on risk for mortality, hospitalizations, falls, and functional decline in older caregivers: four-year follow-up
Keywords: Cuidadores; Mortalidade; Gerontologia; Geriatria; Enfermagem; Carers; Mortality; Gerontology; Geriatrics; Nursing; CIENCIAS DA SAUDE